InCtrl HD intuitive user interface control using Wii remote for high definition videoconferencing - Angco, Marc Jordan G.
High Definition (HD) has become a popular method of distributing media and the increasing availability of high-bandwidth and low-cost Internet services has also increased the demand for the HD videoconferencing systems. Current HD videoconferencing systems deliver lifelike quality, however, some have complex user interface (UI) devices that adds cost to the videoconferencing system, or they simply do not have easy-to-use UI. A possible UI device alternative to the videoconferencing system is the Nintendo Wii Remote Control (Wiimote). The Wiimote has lesses buttons than a standard remote control and uses Infrared (IR) technology to act as a mouse pointer and Bluetooth to communicate with a computer and interact with components on a screen. It can act both as a mouse device and remote control, taking advanctage of both devices. The objective of this project-InCtrl HD- was to develop an HD videoconferencing system with an intuitive UI using an existing videophone with a videomail system, Visiovox. An HDV format media streamer and different media player was integrated with the system to support HD resolution of 1920x1080 pixels at a frame rate of 30fps. The user interface was also modified for use with the Wiimote, to support wireless IR pointer and motion gestures. InCtrl HD can also support multicasting both as a sender or a receiver of the video stream. The Multicasting mode of the system was tested by sending and receiving a multicast stream using InCtrl HD. The test was able to stream HD video to the three endpoints successfully. Quality of Experience (QoF) metrics such as communication end-to-end delay, audiovisual and conversational quality were done to evaluate the usability and ease of using the UI with Wiimote as its control device. The subjective audiovisual MOS tests passed the acceptable rating. The end-to-end delay, however, was found to be higher than the recommended acceptable delay by ITU-T. To asses the users' perception of the delay and impact on communication using the system, MOS on conversational quality was performed. Despite the delay, the MOS for conversational quality was found to be between Good to Excellent, thus delay is still acceptable to users. From the usability tests, System Usability Scale (SUS) score obtained was 64.5% which is higher that the acceptable value, indicating that the system is still generally usable.